Experiential learning theory (ELT)-based classical guidance model to improve responsible character - Juster Donal Sinaga; Kristina Betty Artati (SCHOULID: Indonesian Journal of School Counseling, 2017)
This research aims to: (1) determine the improvement of responsible character of students before and after experiencing character education based on classical guidance service using Experiential Learning Theory (ELT) approach; (2) determine the effectiveness of character education based on classical guidance service ELT approach. This is a quantitative study using pre-experimental One-Group Pretest-Posttest Design. The data collection used Responsible Character Questionnaire with reliability 0.788 in Alpha Cronbach. Subjects in this study were 30 students of class VII A batch 2014-2015 in Kanisius Junior High Schools, Yogyakarta. The results of the study show that: (1) there is an improvement in responsible character of students before and after experiencing seen from the score distribution in each category and from the average score; (2) based on the t-test, there is a significant improvement in the students' responsible character in the Sig. value of (2-tailed) (0.001)<(0.05). Therefore, the implementation of classical guidance service using ELT approach is effective in improving the students' responsible character.